Neuronal and Cognitive Plasticity: A Neurocognitive Framework for Ameliorating Cognitive Aging - Greenwood, Pamela M.; Parasuraman, Raja (Frontiers in Aging Neuroscience, 2010)
What is the neurocognitive basis for the considerable individual differences observed in functioning of the adult mind and brain late in life? We review the evidence that in healthy old age the brain remains capable of both neuronal and cognitive plasticity, including in response to environmental and experiential factors. Neuronal plasticity (e.g. neurogenesis, synaptogenesis, cortical re-organization) refers to neuron-level changes that can be stimulated by experience. Cognitive plasticity (e.g. increased dependence on executive function) refers to adaptive changes in patterns of cognition related to brain activity. We hypothesize that successful cognitive aging requires interactions between these two forms of plasticity. Mechanisms of neural plasticity underpin cognitive plasticity and in turn, neural plasticity is stimulated by cognitive plasticity. We examine support for this hypothesis by considering evidence that neural plasticity is stimulated by learning and novelty and enhanced by both dietary manipulations (low-fat, dietary restriction) and aerobic exercise. We also examine evidence that cognitive plasticity is affected by education and training. This is a testable hypothesis which could be assessed in humans in randomized trials comparing separate and combined effects of cognitive training, exercise, and diet on measures of cognitive and brain integrity. Greater understanding of the factors influencing the course of cognitive aging and of the mechanisms underlying those factors could provide information on which people could base choices that improve their ability to age successfully.